2013
DOI: 10.1111/cxo.12019
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of vitreomacular traction: a case series

Abstract: Three patients had unilateral vitreomacular traction (VMT) syndrome and the diagnosis was confirmed by spectral domain‐type optical coherence tomography (OCT). All patients were female aged 51, 55 and 62 years. All denied surgical intervention. In one patient, rapid spontaneous resolution of the vitreomacular traction with a complete posterior vitreous detachment (PVD) and a normal foveal contour was achieved within 15 days. In the remaining two cases a complete PVD could be detected as late as seven months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] A recent synthesis of the literature on the safety and effectiveness of PPV for VMT revealed that only one-third of eyes gained two or more Snellen lines. 10 Equally, observation may have disadvantages, with a natural history study reporting that only 11% of eyes showed spontaneous resolution over a mean follow-up of 5 years, whereas 64% of eyes lost at least 2 Snellen lines over this timeframe.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] A recent synthesis of the literature on the safety and effectiveness of PPV for VMT revealed that only one-third of eyes gained two or more Snellen lines. 10 Equally, observation may have disadvantages, with a natural history study reporting that only 11% of eyes showed spontaneous resolution over a mean follow-up of 5 years, whereas 64% of eyes lost at least 2 Snellen lines over this timeframe.…”
mentioning
confidence: 99%
“…Given the high rates of PCMO generally in the DM populations, it is fair to conclude pharmaceutical management is suboptimal, and future efforts should be directed towards de-DOI: 10.1159/000521053 veloping more evidence-based medical therapies. For patients with VMT and DM before undergoing cataract surgery, it may be beneficial to undergo a vitrectomy to reduce the chances of developing post-operative PCMO or delaying cataract surgery for spontaneous resolution of VMT which has been observed in 11% of cases within 15 months [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…4 Newer studies, however, have suggested that spontaneous resolution might be more common than previously thought. 5,6 Vitreomacular traction is subclassified on the basis diameter of vitreous adhesion to the macular surface, with an attachment of #1,500 mm or .1,500 mm defined as focal or broad VMT, respectively. 1 Treatment options for focal symptomatic VMT include pharmacological vitreolysis, pneumatic vitreolysis (PV), and pars plana vitrectomy (PPV).…”
mentioning
confidence: 99%
“…4 Newer studies, however, have suggested that spontaneous resolution might be more common than previously thought. 5,6…”
mentioning
confidence: 99%